Switching of Hormone Therapies in Breast Cancer Women - Medeiros, Luana Moreira de; Stahlschmidt, Rebeca; Ferracini, Amanda Canato; Souza, Cinthia Madeira de; Juliato, Cassia Raquel Teatin; Mazzola, Priscila Gava (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective The objective of the present study was to analyze the reasons that led to hormone therapies (HTs) regimen changes in women with breast cancer.Methods This was a retrospective cross-sectional study from a single-institution Brazilian cancer center with patient records diagnosed with breast cancer between January 2012 and January 2017.Results From 1,555 women who were in treatment with HT, 213 (13.7%) women had HT switched, either tamoxifen to anastrozole or vice-versa. Most women included in the present study who switched HT were > 50 years old, postmenopausal, Caucasian, and had at least one comorbidity. From the group with therapy change, ‘disease progression’ was reason of change in 124 (58.2%) cases, and in 65 (30.5%) patients, ‘presence of side effects’ was the reason. From those women who suffered with side effects, 24 (36.9%) had comorbidities.Conclusion The present study demonstrated a low rate of HT switch of tamoxifen to anastrozole. Among the reasons for changing therapy, the most common was disease progression, which includes cancer recurrence, metastasis or increased tumor. Side effects were second; furthermore, age and comorbidities are risk factors for side effects.
Keywords: breast cancer; tamoxifen; hormone therapy; aromatase inhibitor; anastrozole